PENGARUH POLA KONSUMSI ISLAMI TERHADAP PRESTASI AKADEMIK PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MALIKUSSALEH - Damanhur Damanhur; Rahmatullah Rahmatullah (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2018)
The pattern of Islamic Consumption is the most important part of a Muslim’s life, because it distinguishes between Muslims and non-Muslims. As a Muslim not all of the foods can be consumed, there are rules and bans that bind in it so that it has effect to its life activity in this world. The purpose of this study is to obtain the empirical evidence that the pattern of Islamic Consumption affects simultaneously on Academic Achievement. This study uses primary data. The population of this study are students of the Economics and Business Faculty University of Malikussaleh who are Muslim and there are 90 respondents in 2015. The method of selecting the sample of this study is by using slovin method. The data analysis using regression analysis. The results of the study showed that the pattern of Islamic Consumption has a positive effect on Academic Achievement, it proved by a significance value of 0.0045 0.05 which means the hypothesis in this study rejected H0 and received Ha. Most of the respondents showed good results on each question between the attitude and behavior of Islamic consumption.